Conceptions of education and health professionals on Inclusive Education: reflections for transforming practices - Camargo Bartalotti, Celina; Yonezaki, Cristiane; do Nascimento, Vanessa; Bradaschia Correa, Marina; Zaghetto de Almeida, Renata; Custódio Manoel, Mariana; Guedes de Carvalho, Mariana; F. O. Alvarez, Ana Paulo (O Mundo da Saúde, 2008)
Inclusion of people with deficiencies has been the subject of debates and studies, particularly in the field of Education, due to the legal reality that guarantees to this segment of the population the right to frequent regular schools, independently of their peculiarities. For the best understanding of this field, this research was delineated that aims to identify conceptions of inclusive education of education and health professionals, in order to identify actions supporting the construction of a school environment devoted to diversity. Subjects were 90 educators working in Children Education and Elementary and Secondary Education, from public and private schools, and 50 health professionals (occupational therapists, phonoaudiologists, physiotherapists, doctors, nurses, psychologists) that work with people having deficiencies. The sample was defined on the basis of the theoretical saturation principle. Data were gathered with a questionnaire in which it was asked to subjects whether they were against the inclusion of pupils with deficiencies in the regular school, absolutely pro or partially pro, and why. From the answer to the question “why?” the following categories of analysis were elaborated (a posteriori): right, conception of deficiency, support, education, attitude and structure. The analysis of the subjects answers points to a conception of deficiencies as illnesses and an idea of pupil with deficiencies as a problem that the school would not be prepared to face. We conclude that the work for the construction of an inclusive school must entail necessarily actions aimed at changing conceptions on deficiency.